(untitled) (E Global Congress, 2025)
Today, increasing investment activity through the development of the securities market is one of the important tasks for the economies of many countries, but in this process a number of problems and obstacles may be encountered. It is advisable to study and analyze ways to comprehensively assess investment activity, establish a system to eliminate various existing problems associated with the growth of investment activity due to the development of the securities market in our country: